Residual Herbicide in Cover Cropping Systems - Lucas O. R. Maia; Leonard B. Piveta; William G. Johnson (Agriculture)
Soil residual herbicides are often applied at cover crop termination to extend the period of weed control and reduce the selection pressure for herbicide resistance. Previous studies indicate that one of the benefits of cover crop use is the increase in the activity of enzymes in the soil. Some enzymes are also responsible for breaking down herbicide molecules. The biodegradation of herbicides in the soil is a natural process that leads to a reduction in the concentration of the parent compound overtime. Although cover crop use can result in the increased activity of soil enzymes, to date, there is no evidence that such increased activity also leads to a reduced persistence of residual herbicides in the soil. However, cover crop use does alter the fate of residual herbicides by interception, with some studies reporting more than 90% interception. Without rainfall or irrigation during the days following its application, the herbicide remains on the plant surface and is ineffective as a weed control tool. Following the integrated weed management approach, the combination of cover crop and soil residual herbicides is a promising alternative to delay the development of new herbicide resistance cases. However, more research is needed to understand the impact of biomass accumulation on residual herbicide fate and to determine the best strategies to improve herbicide placement on cover cropping system. This paper reviews the impact of cover crop use on soil microbial activity and the further degradation of soil residual herbicides as well as the fate of residual herbicides when applied at cover crop termination.